2006
DOI: 10.1590/s1516-44462006000100004
|View full text |Cite
|
Sign up to set email alerts
|

Depression in women infected with HIV

Abstract: Depression in women infected with HIV Depressão em mulheres infectadas pelo HIVA b s t r a c t Objective: The number of women with HIV infection has been on the rise in recent years, making studies of the psychiatric aspects of this condition very important. The aim of this study was to evaluate the prevalence of major depression in women with HIV infection. Method: A total of 120 women were studied, 60 symptomatic (with AIDS symptoms) and 60 asymptomatic (without AIDS symptoms). Sociodemographic data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 23 publications
1
12
1
4
Order By: Relevance
“…According to several studies, this difference can often be attributed to the population studied, surveyed period, and tools used to identify cases of depression. 5,7 In this study, there was no statistically significant association between the presence of depressive symptoms and gender.…”
Section: Discussioncontrasting
confidence: 63%
“…According to several studies, this difference can often be attributed to the population studied, surveyed period, and tools used to identify cases of depression. 5,7 In this study, there was no statistically significant association between the presence of depressive symptoms and gender.…”
Section: Discussioncontrasting
confidence: 63%
“…Studies conducted in Brazil addressing PLWHA report that the prevalence of depressive symptoms may range from 25.8% to 53.5% (Dal-Bó, Manoel, Beltram Filho, Silva, Cardoso & Cortez, 2015;Mello & Malbergier, 2006;Reis et al, 2011;Schimitt & Silva, 2009;Silveira et al, 2012). In this study, 42.3% of the individuals living with HIV/AIDS had depressive symptoms (BDI > 11).…”
Section: Discussionmentioning
confidence: 49%
“…Another study in Brazil also indicated a high prevalence of 25.8% of symptoms of depression among women infected by HIV/AIDS, much higher values when compared with the general female population (9) . These results indicate the necessity of comprehending the factors that increase the risk of depression among women, considering that rates of depression in the world vary from 4% to 10%…”
Section: Discussionmentioning
confidence: 93%
“…Among the various psychiatric disorders frequently identified in people living with HIV/AIDS, depression is the most prevalent. Apart from depression, it has been observed that stressful life events are associated with increased progression of the HIV/AIDS infection (8) , which in turn, increase from three to five times the risk of developing depression (9) . It has been well established that HIV/AIDS infection compromises the quality of life of the sufferer (10) .…”
Section: Introductionmentioning
confidence: 99%